Impact of financial inclusion and institutional quality on banking stability: Lessons from the Asia region - Nugrohowati, Rindang Nuri Isnaini; Ash Shidiqie, Jannahar Saddam (Economic Journal of Emerging Markets, 2025)
Purpose — This study examines the effects of financial inclusion and institutional quality on bank stability. It first examines the effects of banking on the whole Asian region and then the region according to income categories.Method — We use aggregate data from 2013 to 2021 to investigate banking stability in 39 Asian countries and apply the generalized method of Moments (GMM), specifically the first difference GMM and system GMM. In addition, this research uses Principal Component Analysis (PCA) to measure the composite variables of the financial inclusion index and institutional quality index. Findings — The findings demonstrate that overall financial inclusion has a favourable effect on Asian nations' banking systems. However, an examination based on income categories reveals some intriguing results: financial inclusion improves bank stability in lower- and upper-middle-income countries but does not affect high-income countries. In lower-middle-income countries, institutional quality has a detrimental effect on bank stability; in upper-middle-income and high-income countries, it has no effect.Implications — The availability of financial services to households and small and medium-sized enterprises (SMEs) significantly impacts the stability of Asian banks. Several policy recommendations are feasible to implement, including the need for collaboration between banks and the government to broaden banking services to all communities, particularly in lower-middle-income nations.Originality — Analyzing the differences in the impact of institutional quality and financial inclusion variables on banking stability in Asian countries according to income categories.